System-methodological approach on the nature-protecting activities’ planning - T. P. Devyatkova (Юг России: экология, развитие)
The basic instruction and mechanism of the system dialectical methodology apply for structuring the regional protected objects, measures and definition of their priority directions (trends) in modern economic situations are stated. This approach let us to work out ecological programs satisfying the principles of integrity and coordination of all the components of the problem of “concepts of stable development” realization.